Progress on ICAO’s Strategic Objectives and Global Safety Plans. Pandemic safety challenges - Bashta, Oleksandr; Nosko, Pavlo; Bashta (Sheremet), Alla; Povzun, Oleksandr (My University, 2022)
Alleviations to the Standards of the Annexes and its associated system – CCRD, were established as interim measures to support continued operations during the initial stages of the COVID-19 pandemic. However the CCRD system for filing alleviations has been closed and replaced with planning tools, approaches and guidance for the recommencement of operations in line with the requirements of the SARPs.
Keywords: COVID-19 pandemic; safety challenges; World Health Organization; кафедра технології оздоровчих продуктів